Fungal antagonistic activity of rhizobacteria isolated from black pepper - Trinh, Thi Huyen Trang; Nguyen, Van Bon; Doan , Manh Dung; Tran, Minh Dinh; Le, Mai Huong; Nguyen, Anh Dzung (Vietnam Journal of Science and Technology, 2025)
Decline disease associated with Fusarium fungus is serious damage to black pepper and other crops. Biocontrol using rhizosphere bacteria is a sustainable and eco-friendly solution to manage this disease. From the collection, 44 isolates were screened Fusarium antagonistic acitivity. The results showed that Fusarium mycelium growth inhibition activity ranged from 12.50 to 66.25%, and six potent isolates were selected to evaluate the Fusarium antagonistic activity on black pepper seedlings in the greenhouse. These rhizobacterial isolates significantly affected the growth and the rate of Fusarium disease of the seedlings in the greenhouse. The results found the most potential isolate to be Bacillus subtilis RB.CJ41. Furthermore, the Fusarium antagonistic activity of RB.CJ41 was investigated by hydrolysis enzymes and chemical compounds by GC/MS method. It found that chitinase, protease, and beta-glucanase contributed to almost the inhibition. Nineteen major volatile compounds were detected and identified by the GC/MS method. Some volatile compounds produced by RB.CJ41 are antifungal compounds derivatized from Benzoic acid, Triazole, Bromoacetyl, Pyrazole, and Acetamide. Since the Fusarium antagonistic activity, the Bacillus subtilis RB.CJ41 is a promising bacterial strain to apply for the sustainable production of black pepper.